2001
DOI: 10.1144/petgeo.7.s.s17
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scale approach to improve reservoir characterization and forecasting: the Albacora Field (deep-water offshore Brazil) study

Abstract: The Upper Albian Namorado Sandstone is one of the reservoirs of the Albacora Field, located in the Campos Basin, deep-water offshore Brazil. It is a sand-rich turbidite system where the most important controls on permeability are calcite cementation, thin beds of non-reservoir lithologies and some north-south trending faults. A major multidisciplinary reservoir characterization project was conducted to improve the reservoir description using all available data. In this paper, we focus on how the effect of rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…17 shows porosity and water saturations after 0.34 pore volumes injected (PVI) for selected cross-sections of the models. (Slatt and Weimer, 1999;Slatt, 2000;Stephen et al, 2001;Cunha et al, 2001;Larue, 2004;Larue and Friedmann, 2005). 8.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 shows porosity and water saturations after 0.34 pore volumes injected (PVI) for selected cross-sections of the models. (Slatt and Weimer, 1999;Slatt, 2000;Stephen et al, 2001;Cunha et al, 2001;Larue, 2004;Larue and Friedmann, 2005). 8.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Significant effort has been focused upon understanding their architecture and internal sandstone body geometries in order to facilitate reservoirscale facies modelling (see recent examples in Wonham et al, 2000;Cunha et al, 2001;Purvis et al, 2002;Smith and Moller, 2003;Conybeare et al, 2004;Satur et al, 2005). Sedimentological heterogeneities that affect hydrocarbon production can occur at a scale that is both sub-seismic (Slatt and Weimer, 1999;Coleman and Sheppard, 2000;de Araujo Simoes-Filho and Queiroz de Castro, 2001) and less than the typical development well spacing (Hurst et al, 1999).…”
Section: Reservoir Models Turbidite Systems and Outcrop Analoguesmentioning
confidence: 99%
“…In conclusion, it is suggested that the discrete nature of concretions makes an object-based approach [66] the best suited technique for stochastically modelling heterogeneous calcite cementation, in which insertion of objects with different shapes and size can be conditioned to statistics from outcrop analogues similar to CdV.…”
Section: Prediction and Likely Impact On Reservoir Propertiesmentioning
confidence: 99%